The effect of contact lens wear on tear immunglobulins [DER EINFLUSS VON KONTAKTLINSEN AUF DIE IMMUNOGLOBULINE IN DER TRANENFLUSSIGKEIT] - (:unkn) unknown (My University, 1990)
Tear immunoglobulins (IgA, IgG and IgM) were assayed by a radial immunodiffusion technique in 24 contact lens wearers and 22 healthy controls. IgA levels were found to be higher (P≤0,02) in rigid lens wearers (mean = 0,14 ± 0,07 g/l) than in the controls (mean = 0,08 ± 0,06 g/l). IgA levels of both of PMMA wearers (mean = 0,14 ± 0,08 g/l, P ≤ 0,05) and rigid gas permeable lens wearers (mean = 0,13 ± 0,07 g/l, P ≤ 0,05) were higher than in the control group. No statistically significant differences were found between the IgA levels of wearers of various types of soft lenses or between IgG and IgM levels of wearers and controls. The mean duration of lens wear was 6,4 years, ranging from 1 to 20 years. IgG levels increased in correlation to length of lens wear (P ≤ 0,03). These findings suggest that the continuous mechanical stimulation of the conjunctiva alters the level of tear immunoglobulins, especially the IgA type.